Study on characteristics of patients with repeated admissions for asthma in Hospital Tengku Ampuan Afzan, Kuantan, Pahang, Malaysia - Ismail, Shaiful Bahari; Aris, Mohd Aznan Md; Mohamad, Fauzi (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2018)
ABSTRACT (Perlu disediakan makluman di antara 100 - 200 perkataan di dalam Bahasa Malaysia dan Bahasa lnggeris. lni kemudiannya akan dimuatkan ke dalam Laporan Tahunan Sahagian Penyelidikan & Pembangunan sebagai satu cara untuk menyampaikan dapatan projek tuan/puan kepada pihak Universiti). Objective To determine the characteristics in patients with repeated admissions for asthma compared to patients with no repeated admission for asthma over the same period of one-year duration. Methods A cross-sectional comparative study among 30 patients with asthma who had repeated admissions and another 30 patients with asthma who had no repeated admission for exacerbation of asthma over the same period of one-year duration (2001 ). The socio-demographic, clinical characteristics and evaluation data were collected. The evaluation included measurement of peak expiratory flow (PEF), inhaler technique skills and questionnaires on knowledge of asthma. Results There was no significant difference in socio-demographic characteristics, measurement of PEF and inhaler technique skills in both groups. In clinical characteristics, there was significant difference noted in history of atopy, history of absenteeism, asthma symptoms and use of medications. There was significant difference in .the knowledge of asthma where the total mean scores was 14.8 in repeated admissions group and 17.7 in non - repeated admission group from the total sco~e of 31. Conclusions Patients with repeated admissions for asthma tend to have high past history of atopy, high history of absenteeism from work or school, more frequent nocturnal symptoms and more use of low dose inhaler corticosteroids. They also had poor inhaler techniques and less asthma knowledge. USM J/